2012
DOI: 10.1097/olq.0b013e31823b23a4
|View full text |Cite
|
Sign up to set email alerts
|

Declining Syphilis Trends in Concurrence With HIV Declines Among Pregnant Women in Zambia

Abstract: The syphilis prevalence declined by 65% in urban and 59% in rural women. Provincial variations need to be further studied to better guide specific sexually transmitted infection prevention and control programmes in different geographical settings. The national ANC-based HIV and syphilis surveillance system provided good proxies of syphilis prevalence and trends.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
21
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 16 publications
5
21
2
Order By: Relevance
“…These results are in line with other studies on the association between HIV prevalence and educational attainment in sub-Saharan Africa [32], [33], including Zambia [3], [15]. In addition, a similar pattern of marked decrease in syphilis prevalence among educated women was observed in the same ANC data [34]. A likely explanation for this change is that educated people, once equipped with knowledge about HIV from prevention campaigns, have been quicker in changing their sexual behaviour [35], [36], [37], [38], [39], [40], [41].…”
Section: Discussionsupporting
confidence: 91%
“…These results are in line with other studies on the association between HIV prevalence and educational attainment in sub-Saharan Africa [32], [33], including Zambia [3], [15]. In addition, a similar pattern of marked decrease in syphilis prevalence among educated women was observed in the same ANC data [34]. A likely explanation for this change is that educated people, once equipped with knowledge about HIV from prevention campaigns, have been quicker in changing their sexual behaviour [35], [36], [37], [38], [39], [40], [41].…”
Section: Discussionsupporting
confidence: 91%
“…The burden of syphilis among this population of pregnant women in rural South China is also similar to what has been reported in studies conducted at regional blood donation centers that cover urban and rural areas throughout China (0.30–0.63%) [19][21]. Compared to other countries, the prevalence reported here is lower than among pregnant women in rural low-income settings in sub-Saharan Africa and Haiti [22][30] but higher than among women in rural areas in high-income countries like the U.S. [31] The syphilis epidemic among pregnant women in rural Guangdong province might be partially explained by female migrants or their husbands returning to their rural origins from the cities with untreated syphilis and persistently risky sexual behavior [32]. Studies have found that migrants in some Chinese cities have high-risk sexual behavior [33] and a higher prevalence of syphilis compared to local residents [16], [17], but few studies have examined the sexual risk of returning migrants.…”
Section: Discussionsupporting
confidence: 86%
“…This does not correspond with the findings from 5 rounds of syphilis surveillance among pregnant women in Zambia between 1994–2008 which showed consistently lower risk of syphilis in higher educated women [28]. It is likely that GUD is substantially under-reported in this population-based survey, and therefore this lack of association could be explained by differential reporting bias, i.e.…”
Section: Discussioncontrasting
confidence: 74%